1982
DOI: 10.3102/00028312019004598
|View full text |Cite
|
Sign up to set email alerts
|

Consequences in High School and College of Sex Differences in Mathematical Reasoning Ability: A Longitudinal Perspective

Abstract: Between 1972 and 1974 the Study of Mathematically Precocious Youth (SMPY) identified over 2,000 7th and 8th graders who scored as well as a national sample of 11th and 12th grade females on the College Board’s Scholastic Aptitude Test (SAT) Mathematics or Verbal tests. A substantial sex difference in mathematical reasoning ability was found (Benbow & Stanley, 1980b, 1981). The consequences and development of this sex difference over the following 5 years were investigated longitudinally. Over 91 percent (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(78 citation statements)
references
References 16 publications
2
76
0
Order By: Relevance
“…Few major writers, artists, or scientists emerged from this 'genius' level IQ group. Other wellknown longitudinal studies of giftedness, however, demonstrated higher levels of creative achievement in adulthood; these include Julian Stanley's Study of Mathematically Precocious Youth (SMYP; Benbow & Minor, 1986;Benbow & Stanley, 1982;Lubinski & Benbow, 1994;Stanley & Benbow, 1982) and Rena Subotnik's longitudinal examination of 1983 Westinghouse semi-finalists (Subotnik & Steiner, 1994;Subotnik, Duschl, & Selmon, 1993).…”
Section: Age Giftedness and Scientific Achievementmentioning
confidence: 96%
“…Few major writers, artists, or scientists emerged from this 'genius' level IQ group. Other wellknown longitudinal studies of giftedness, however, demonstrated higher levels of creative achievement in adulthood; these include Julian Stanley's Study of Mathematically Precocious Youth (SMYP; Benbow & Minor, 1986;Benbow & Stanley, 1982;Lubinski & Benbow, 1994;Stanley & Benbow, 1982) and Rena Subotnik's longitudinal examination of 1983 Westinghouse semi-finalists (Subotnik & Steiner, 1994;Subotnik, Duschl, & Selmon, 1993).…”
Section: Age Giftedness and Scientific Achievementmentioning
confidence: 96%
“…Many of the studies examining the effects of background on mathematical performance have focused on the relation between sex and courses taken. It is well documented that males take more mathematics courses than females (Armstrong 1981;Benbow and Stanley 1982;Fennema and Sherman 1977). Several studies have found that controlling for course-taking substantially reduces.…”
Section: Introductionmentioning
confidence: 99%
“…For both men and women, mathematical self-confidence after four years of college is most strongly predicted by factors pertaining to precollege experiences: initial math self-confidence, SAT scores, an initial interest in science, and for women only, having higher grades and greater math and science preparation in high school. Providing students, especially women, with early preparation and encouragement has been a major recommendation in a number of studies and reports (Benbow and Stanley, 1982; Ethington and Wolfle, 1984; Meece et al, 1982;Sherman, 1982Sherman, , 1983. Echoing previous suggestions, findings from this study suggest that in order to develop students' mathematical self-confidence, all students, and women in particular, should be encouraged to take more math courses in high school, They 160 SAX should receive positive reinforcements for their accomplishments, and should be encouraged to express confidence in their intellectual abilities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%